Rare Case of High Voltage Electric Injury Resulting in Bowel Perforation: A Successful Management with Diversion Colostomy - Mohamed Arsath Shamsudeen; Uday Singh Dadhwal; Suresh V Chinni, (Malaysian Journal of Science (MJS), 2025)
Electrical injuries are categorized into low-voltage injuries (<1 kilovolt) and high-voltage injuries (>1 kilovolt). Electrical injuries usually present with an entry wound at the site of contact and an exit wound where the current leaves the body. Bowel perforation caused by an electric current is a rare but serious complication. We report a case of a high-voltage electric burn with entry wounds on both hands and an exit wound on the right foot, complicated by descending colon perforation, which presented late with peritonitis. The patient was successfully treated with a diversion colostomy and subsequent takedown. This case highlights the potential for significant internal injuries, such as bowel perforation, following high-voltage electrical injuries and emphasizes the importance of timely surgical intervention for such complications.